Geometric design of roads handbook - Wolhuter, K. M. (CRC Press/Taylor & Francis, 2015)
A practical guide for graduate students taking geometric design, traffic operations/capacity analysis, and public transport, the Geometric Design of Roads Handbook introduces a novel approach that addresses the human aspect in the design process and incorporates relevant concepts that can help readers create and implement safe and efficient designs.